Exploring the Nexus: Cyberlaw and Artificial Intelligence Research Trends - Indriavita, Dela Cornelia Helen; Purwaningsih, Sri Budi; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This dataset, "Cyberlaw OR Cyber Law AND Artificial Intelligence: A Comprehensive Study," meticulously analyzes 2,345 journal articles from Lens.org, examining the intersection of Cyberlaw and Artificial Intelligence. Employing systematic methodologies, the study highlights trends: University of Liverpool leads, Computer Science dominates, with prolific authors like Giovanni Sartor. Global impact is evident with the UK as an active contributor. Top publishers, including Springer Nature, contribute significantly. This resource offers nuanced insights into this complex legal-tech interaction, benefiting researchers, students, and journalists for informed decision-making and future studies in Cyberlaw and AI. Highlights : Detailed analysis of Cyberlaw and Artificial Intelligence intersections from Lens.org. Dominance of Computer Science and notable contributors like Giovanni Sartor. Global impact and insights aiding informed decisions in this critical legal-tech domain. Keywords: Cyberlaw, Artificial Intelligence, Journal Articles, Research Trends, Scholarly Publications